Local Government Migrant Policies in Tokyo, Japan : National Exclusion, Local Inclusion. - Nagy, Stephen R. (Edwin Mellen Press, 2012)
The book documents the movements of migrant populations through Tokyo. It reveals how the local government makes policies that impact the practice of multicultural co-existence. The author draws on extensive in depth interviews with government officials and his own 4-year tenure as the International Relations Coordinator in a local government in Tokyo. His findings demonstrate that in contemporary Japan, the integration of foreigners is being led by local governments. There are many factors contributing to immigration into Japan. With Japan facing a labor shortage this book examines policies t.